FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU TIDAK AMAN PEKERJA BAGIAN LAMBUNG GALANGAN KAPAL PT X - Jessica Sangaji; Siswi Jayanti; Daru Lestantyo (Jurnal Kesehatan Masyarakat (Undip), 2018)
One of the causes of accidents is unsafe behavior. Unsafe behavior can be caused by 3 factors: predisposing factors, enabling factors, and reinforcing factors. Percentage of accidents due to the most unsafe behavior in PT X is in hull section. The purpose of this study was to analyze the correlation between age, work period, education, knowledge, attitude, OHS training, availability of OHS facilities, supervision with unsafe behavior of PT X shipyard hull section. The type of this study is an analytic observasional with cross sectional research approach. The subjects of this study were 40 workers of PT X shipyard in hull section. Data collection was carried out using a questionnaire instrument. Statistical analysis using the Spearman test. The test results show that there is a correlation between knowledge (p = 0.037), attitude (p value = 0.044), supervision (p value = 0.037), OHS training (p value = 0.030) and availability of OHS facilities (p value = 0.043) with unsafe behavior. There was no correlation between age (p value = 0.504), work period (p value = 0.211), education level (p value = 0.186) and unsafe behavior. Suggestions for the owner of the company are to conduct socialization about OHS regularly every month, improve OSH training programs for workers, immediate replacement of damaged PPE to the newest one.